One pot solvent free synthesis and in vitro antitubercular screening of 3-aracylphthalides against mycobacterium tuberculosis - Limaye, Rohan A.; Kumbhar, Virendra B.; Natu, Arun D.; Paradkar, Madhusudan V.; Honmore, Varsha S.; Chauhan, Rubia R.; Gample, Suvarna P.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2013)
One pot synthesis of 3-Aracylphthalide was accomplished in good yield by reacting 2-carboxy benzaldehyde with various aromatic methyl ketones in presence of methane sulphonic acid. Various phthalides thus obtained were characterized with spectral techniques. These phthalides were subjected to in vitro antitubercular screening against Mycobacterium tuberculosis H37Ra (MTB) by using XRMA protocol. Among the phthalides screened, four exhibited half maximal inhibitory concentration (IC50) in the range of 0.81-1.24 mu g/ml thereby providing potential lead compounds for future drug discovery studies. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: 3-Aracylphthalide; Antitubercular activity; Methane sulphonic acid; One pot synthesis